Becoming invisible: The ethics and politics of imperceptibility. Issue 1 (1st January 2018) - Smith, Warren; Higgins, Matthew; Kokkinidis, George; Parker, Martin
Abstract : This speculative essay examines 'invisible' social identities and the processes by which they are manifested and occasionally sought. Using various literary and academic sources, and loosely informed by an unlikely combination of Stoic philosophy and post-structuralist politics, we argue that invisibility is conventionally viewed as undesirable or 'suffered' by individuals or groups that are disadvantaged or marginalised within society. Whilst appreciating this possibility, we argue that social invisibility can also be the result of strategies carefully conceived and consciously pursued. We suggest that forms of social invisibility can be acquired by ethically informed personal action as well as by politically informed collective action. In this context, invisibility can be seen as a strategy of escaping from institutionalised and organisational judgements and which presents a challenge to common notions of voice and identity.